Improving the Ability to Solve Mathematical Problems based on Higher Order Thinking Skills (HOTS) through Team Assisted Individualization (TAI) - Lintang Permatasari (Hipotenusa : Journal of Mathematical Society, 2020)
The research aims to improve the ability of students insolving problems based on Higher Order Thinking Skills (HOTS) subjects Mathematics material bangun ruang sisi datar with the use of learning models Team Assisted Individualization (TAI).  This research uses the Research method Classroom Action (CAR) with two cycles, where each cycle consists of four stages, namely planning, implementation, observation, and reflection. Data analysis using the percentage formula, if completeness is ≥ 85%, the cycle is terminated sign that the research has been successful.  Based on research that has been done, obtained the increase in students completeness from the pre cycle results was 19.4%, in the first cycle amounted to 77.4%, and in the second cycle of 89.7%.  This shows that the use of the Team Assisted Individualization (TAI) learning model can improve the ability to solve questions based on Higher Order Thinking Skills (HOTS) subject mathematics material to bangun ruang sisi datar in students VIII grade of SMP Negeri 1 Juwangi in the academic year 2019/2020.